2001
DOI: 10.2166/wst.2001.0826
|View full text |Cite
|
Sign up to set email alerts
|

Microbial indicator removal in onsite constructed wetlands for wastewater treatment in the southeastern U.S.

Abstract: Seven onsite constructed wetlands for wastewater treatment in the coastal plains of Alabama and North Carolina were studied from September 1997 to July 1998. Each site was examined for its ability to remove a range of fecal contamination indicators from settled wastewater. Indicator organisms include total and fecal coliforms, enterococci, Clostridium perfringens, and somatic and male-specific (F+) coliphages. Four identical domestic wastewater treatment sites in Alabama were evaluated. In these sites the Log1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…[3][4][5][6] Wetlands can efficiently remove nutrients and enteric microorganisms but they are not suited to a subarctic climate with a harsh winter with ice and snow cover on the soil for several months. In addition, their reduction rates of enteric microorganisms tend to be retarded if the temperature is low.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Wetlands can efficiently remove nutrients and enteric microorganisms but they are not suited to a subarctic climate with a harsh winter with ice and snow cover on the soil for several months. In addition, their reduction rates of enteric microorganisms tend to be retarded if the temperature is low.…”
Section: Introductionmentioning
confidence: 99%
“…Routine monitoring of water and produce for NV would help improve the safety of fresh produce (3,4,7,16). However, methods for routine detection of NV in the environment are currently not available.…”
mentioning
confidence: 99%
“…They recommend that animal carcasses, including birds and fish, during an outbreak, be burned rather than buried to mitigate the cycle. Other researchers have demonstrated that wetlands with emergent vegetation could result in 1.6 to 2.9 log 10 reductions in C. perfringens spores from treated sewage (Barrett et al 2001). Perhaps in areas of concern, best management practices (BMPs) could be constructed to retard hydraulic mobilization of botulinum type as the raw water storage area; however, no spores were detected after coagulation, nor were they found after final rapid or slow sand filters (Notermans et al 1980).…”
Section: Several Researchers Have Applied Mathematical Modelsmentioning
confidence: 99%